Diseño de válvulas de impulso check para bomba de ariete multipulsor bóxer de dos vías de carga horizontal. - Bedón Velasco, Edgar Abel (2021)
This thesis is focused on producing changes in the spring valves coupled to the horizontally loaded two-way boxer multipulsor hydraulic ram pump from low volumetric, hydraulic and mechanical performance, proceeding to an analysis of components, variables and operation. In general, maintaining a greater emphasis on the delivery valves, the methodologies are designated from the operating principle of the hydraulic ram pump, which is deduced based on the water hammer caused by the delivery valves, the alternation of the fluid in movement and the determination of energies for the pumping activation, the design methodologies are implemented through the ANSYS software and the sizing of modified check valves with an adjustable opening system, to improve the aforementioned parameters. Through the designation of variables we obtain the equations stipulated for the assigned parameters, based on the calculation of the force provided by the flow inside the pipe, this being (21.51 N) when it hits the inner face of the cover dimensioned based on the API 594 standard and a selection of ASTM A36 material, this force allows us to simulate an external adjustable mechanism analyzed by means of a free body diagram, by assimilating test cases to verify the best link dimension by comparing speeds, opting for the of higher performance, thus the maximum closing and opening speed of the check valve is 700 mm/s in cycles of 0.2 seconds, the 81mm lid diameter has a closing and opening period equal to 0.3 seconds. The joints identified as reactions in the free-body diagram produce a periodic oscillatory movement of the lid, generating a performance difference of 0.94 with respect to the previous design for an inlet flow of 0.005 3 ⁄, we proceed to the manufacture of this mechanism after an analysis of stresses, displacement and safety factor which include favorable results for its validation.